Understanding and visualizing schedule deviations in construction projects using fault tree analysis - Hsu,P-Y; Aurisicchio,M; Angeloudis,P; Whyte,J (Engineering, Construction and Architectural Management, 2020)
Delays in construction projects are both disruptive and expensive. Thus, potential causes of schedule deviation need to be identified and mitigated. In previous research, delay factors were predominantly identified through surveys administered to stakeholders in construction projects. Such delay factors are typically considered individually and presented at the same level without explicitly examining their sequence of occurrence and inter-relationships. In reality, owing to the complex structure of construction projects and long execution time, non-conformance to schedule occurs by a chain of cascading events. An understanding of these linkages is important not only for minimising the delays but also for revealing the liability of stakeholders. To explicitly illustrate the cause–effect and logical relationship between delay factors and further identify the primary factors which possess the highest significance toward the overall project schedule delay, the fault tree analysis (FTA) method, a widely implemented approach to root cause problems in safety-critical systems, has been systematically and rigorously executed.